Lithium Battery Degradation and Failure Mechanisms: A State-of-the-Art Review - Joselyn Stephane Menye; Mamadou-Baïlo Camara; Brayima Dakyo (Energies)
This paper provides a comprehensive analysis of the lithium battery degradation mechanisms and failure modes. It discusses these issues in a general context and then focuses on various families or material types used in the batteries, particularly in anodes and cathodes. The paper begins with a general overview of lithium batteries and their operations. It explains the fundamental principles of the electrochemical reaction that occurs in a battery, as well as the key components such as the anode, cathode, and electrolyte. The paper explores also the degradation processes and failure modes of lithium batteries. It examines the main factors contributing to these issues, including the operating temperature and current. It highlights the specific degradation mechanisms associated with each type of material, whether it is graphite, silicon, metallic lithium, cobalt, nickel, or manganese oxides used in the electrodes. Some degradations are due to the temperature and the current waveforms. Then, the importance of thermal management and current management is emphasized throughout the paper. It highlights the negative effects of overheating, excessive current, or inappropriate voltage on the stability and lifespan of lithium batteries. It also underscores the significance of battery management systems (BMS) in monitoring and controlling these parameters to minimize the degradation and the risk of failure. This work provides a summary of valuable insight into the development of BMS. It emphasizes the importance of understanding the degradation mechanisms and failure modes specific to different families of lithium batteries, as well as the critical influence of temperature and current quality. Rational management or efficient controlling of these parameters can enhance the performance, reliability, and lifespan of lithium batteries.